PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR BAHASA MANDARIN SISWA DI EDU SMART LEARNING CENTRE 论电教媒体对快乐中文补习班学生学习汉语的影响 - Cynthia Hualangi (Journal of Language, Literature and Teaching, 2022)
Audio-visual media is a medium that comprise of sound and image elements, such as films or videos, which can be utilised to deliver learning materials in a more interesting way, including visualising teaching materials, so that students are more keen on studying. This research aims to determine significantly the influence on the use of audio-visual media on Chinese language learning outcomes of L3-level students at Edu Smart Learning Centre and is expected to increase teachers' insights into teaching methodologies as well as deepen their understanding of the functionality of audio-visual media, so that it can be applied in teaching Chinese language.The learning material used for teaching L3-level students at Edu Smart Learning Centre is Kuai Le Zhong Wen, the Chinese language book used at Edu Smart Learning Centre and is for own use.This research is conducted at Edu Smart Learning Centre, especially towards L3A and L3B students. It uses pretest-posttest control group design with one type of treatment. The analysis of the research outcome is t-test analysis. The given treatment is the usage of audio-visual media.The research outcome shows that, with the application of audio-visual media, the Chinese language learning outcomes of L3-level students at Edu Smart Learning Centre are better. This concludes that audio-visual media affects the Chinese language learning outcomes of L3-level students at Edu Smart Learning Centre significantly. Keywords: Audio-visual Media, Learning Outcome, Chinese Language